Interleaved Bidirectional DC-DC Converter Operation Strategies and Problem Challenges: An Overview - Syah, Mario Norman; Firmansyah, Eka; Utomo, Dzuhri Radityo (2022)
A bidirectional dc-dc converter is an important topology for interfacing different voltage levels in both power flow directions. It can be applied to hybrid energy storage systems (HESS), electric vehicles, dc microgrids, and many other applications. The topology can be interleaved in order to gain advantages such as current and voltage ripple reduction and increase power handling capability. The interleaved bidirectional converter has to operate in a specific conduction mode to avoid the losses due to high-frequency switching and reverse recovery diode. There are many interleaved bidirectional converters that have been proposed. This paper tries to review some of those proposed papers from the point of view of conduction mode, control strategy, and their challenges. This review aims to provide a comparative basis for developing new approaches of interleaved bidirectional converters for specific applications.